Elaboração de um método de análise dos sonhos na terapia de casal: um enfoque junguiano - Pessoa, Maria Silvia Costa (2011)
The objective of this research is to propose a method to work with dreams in couple therapy based on the analytical psychology of C. G. Jung and others Jungian authors and the clinical experience of the researcher as a couple therapist. Two couples participated in this research. These couples were experiencing conjugal conflicts and had been in a stable relationship for more than one year. The first couple attended a total of 15 weekly sessions and 8 dreams were considered during this period. The second couple attended a total of 16 weekly sessions and 6 dreams were considered during this period. We adopted a qualitative method, which permitted a deeper understanding to be obtained of the psychic processes, and dreams were used as a therapeutic instrument. The method for working with dreams emerged and was systematized based on the sessions with the couples, when the dreams were told and investigated. The results suggested that it is possible to develop a method to work with dreams within the context of couple psychotherapy, with this method systematized into three stages: the couple s dream, consideration ad reflection. The research also suggests that working with dreams can help the couple amplify their vision of the conflict, increase the self-perception of each spouse from participating in the couple problematic, reveal the dysfunctions in the pattern of the couple s dynamic and highlight the changes necessary to recover the individuation process within the marriage